Seasonal variation and sources estimation of PM2.5bound pahs from the ambient air of Chiang Mai City: An all-year-round study in 2017 - Sawaeng Kawichai (2020)
© 2020, Chiang Mai University. All rights reserved. This study investigated PM2.5-bound polycyclic aromatic hydrocarbons (PAHs) concentration to estimate sources of air pollution in Chiang Mai City, Thailand. In this study, the ambient PM2.5 samples were collected from January to December 2017 in Chiang Mai City (18° 47′ N, 98° 57′ E). Sixteen PAHs that have been designated as high priority by the US EPA were analyzed using a gas chromatograph (Model 7890A, Agilent) equipped with a mass spectrometer detector (Model 5975C). The PM2.5 concentrations could be classified into two periods by using active fire data (or so-called number of hotspots) detected by Moderate Resolution Imaging Spectroradiometer, a type of remote satellite sensing imaging. The first period took place from January to May, as a result of high biomass burning (HBB; n=62) and the second period occurred from June to December due to low biomass burning (LBB; n = 58). In both periods there was a significant difference between the 24-hour mean concentrations of PM2.5 ranging from 6.07-79.9 µg/m3 with a mean±SD of 35.8±16.3 µg/m3 for the HBB period and 7.71-53.4 µg/m3 with a mean±SD of 24.6±10.4 µg/m3 for the LBB period. Meanwhile, the mean concentrations of the 16 PAHs in the HBB period were significantly higher than those in the LBB period (p<0.01). The mean concentration of total PAHs in the HBB period was 9.22±3.11 ng/m3 as compared to 3.51±1.85 ng/m3 in the LBB period. The mean concentration of tPAHs in the HBB period was significantly higher than those in the LBB period (p<0.01). Molecular diagnostic ratios and principle component analysis of individual detected PAHs were used to characterize and identify their possible sources. The results indicated that biomass burning was the primary source of PAHs in the HBB period while fuel combustion and biomass burning were the sources in the LBB period. The present study results therefore suggest that a year-round study was able to estimate the sources of PM2.5-bound PAHs from the ambient air of Chiang Mai City.